Social and Emotional Learning during Pandemic-Related Remote and Hybrid Instruction: Teacher Strategies in Response to Trauma - Rebecca S. Levine; Rebecca J. Lim; Amy Vatne Bintliff (MDPI AG, 2023)
Schools play an important role in fostering student intrapersonal and interpersonal skills and development, also known as social and emotional learning (SEL). This study examined how K-12 teachers used student SEL strategies in remote and hybrid classroom environments during the COVID-19 pandemic, a time of heightened distress and trauma. Survey data were collected from 26 teachers in Southern California and follow-up semi-structured interviews were conducted with 16 teachers. Responses were analyzed from an integrated SEL- and trauma-informed perspective. Themes that emerged included focusing on relationships; building routines and predictability; creating space to identify and share feelings; incorporating movement, mindfulness, and play; implementing culturally affirming practices; providing student choice and leadership; and engaging and collaborating with families. Various challenges associated with implementing SEL during COVID-19 are discussed, including teacher burnout, being unsure who was listening in on class conversations, and feeling disconnected in an online environment. Recommendations for practice and further research are provided.